New perspectives in econometric theory - White, Halbert (Cheltenham ; Northampton, Mass. : Edward Elgar, 2004)
This work presents the most important published work of Halbert White on econometrics. With new introductions to each of the chapters, these articles cover work from the early 1980s to 1996. Using rigorous mathematical techniques White develops many of the central themes of econometrics.
Includes bibliographical references and index.
oif 25/07/16
Loans
Keywords: Econometrics